Standard Operating Procedure – The Backbone of GMP (Homoeopathy for All, 2024)
Standardisation is defined as an  activity that gives rise to solutions  for repetitive use of the activity.  Generally, the activity constitutes  the process of establishing and  implementing standards. Thus,  SOPs (Standard Operating  Procedures) are the perfect result  of a standardisation activity. High  levels of quality are important to  accomplish manufacturer’s business  objective. SOP is a back bone of any  pharmaceutical industry, having a  deep symbiotic relationship between  compliance and quality. SOPs  are intended to be specific to the  organisation or a particular facility. A  well written SOP reflects the image  of the company. The current article  focuses mainly on the definition of  SOP, its significance and benefits,  types of SOPs, writing style, formats  of SOP and its use.
Keywords: Standard; Operating